Asmara: Africa's Modernist City (UNESCO World Heritage Nomination). Issue 1 (2nd January 2017) - Denison, Edward; Teklemariam, Medhanie; Abraha, Dawit
Abstract : In January 2016, the State of Eritrea submitted its first ever application to UNESCO for inscription on the World Heritage List (WHL). The nominated site was the country's modernist capital, Asmara. The 1, 300-page Nomination Dossier represents the distillation of nearly two decades of collaborative research by professionals from a wide range of disciplines in Eritrea and overseas, supported by many national and international government agencies and non-governmental organisations. This paper seeks to summarise the enormous quantity of work contained in the Nomination Dossier and its most important propositions and findings. Asmara is an outstanding example of a colonial capital that bears witness to the universal encounter with modernity in the twentieth century and consequent postcolonial experiences. The historic urban landscape embodies in a whole city the unity of innovative urban planning and modernist architecture combined with local natural and cultural conditions. An urban planning process based on functional and racial zoning demonstrates the Italian colonial response from the late-nineteenth century to the challenges of modern urban requirements in a highland African setting. The architectural character exemplifies a period of intense development in the 1930s that coincided with the global proliferation and artistic apogee of pre-war modernism and its various forms. The research challenges conventional perceptions based on universalistic norms, inviting a reassessment of how colonial heritage and modernism are perceived beyond the Eurocentric gaze. Eritrea's decision to conserve Asmara's early colonial era architecture represents a profoundly different attitude towards architectural heritage and its interpretation and treatment compared with many other post-colonial settings. Asmara's nomination also presents an opportunity to encourage critical reflections on cultural relations and heritage globally, and to promote stability and prosperity locally. The three main aims of the research are: to implement the necessary measures for managing the conservation of Asmara's heritage assets; to ensure the city's successful inscription on the WHL; and to contribute to redressing the comparative under-representation of African and modernist sites on the WHL.